2021
DOI: 10.1128/spectrum.00080-21
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Its Dynamics of Filamentous Fungi from Clinical Specimen Cultures: An Extensive Study

Abstract: Fungal culture is the gold standard method of diagnosing fungal infections, but important information, such as the impact of media and incubation times on fungal recovery, is not well documented. This study addressed these gaps using extensive data-based evaluation focused on molds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(24 reference statements)
0
5
0
Order By: Relevance
“… Long turn-around-time; in case of yeasts, up to five days, and moulds up to four weeks; Qualification to select the proper medium; Long-delayed targeted treatment; Prone to contaminations; Low sensitivity for candidemia and aspergillosis. [ 35 , 50 , 173 ] Microscopy Visualization of fungal structures; Analysis of shape, tracking of motion, and classification of microorganisms; Visualization of fungal biofilm formation. Does not allow fungal genus or species identification; Similar microscopic appearance of several fungus.…”
Section: Methods Used For Proven Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“… Long turn-around-time; in case of yeasts, up to five days, and moulds up to four weeks; Qualification to select the proper medium; Long-delayed targeted treatment; Prone to contaminations; Low sensitivity for candidemia and aspergillosis. [ 35 , 50 , 173 ] Microscopy Visualization of fungal structures; Analysis of shape, tracking of motion, and classification of microorganisms; Visualization of fungal biofilm formation. Does not allow fungal genus or species identification; Similar microscopic appearance of several fungus.…”
Section: Methods Used For Proven Diagnosismentioning
confidence: 99%
“…To improve mould detection by culture, Bao et al [ 50 ] analysed the effect of different culture media and time of incubation of 1,821 moulds (hyaline, dematiaceous, Onygenales and Mucorales) isolated from 1,687 patients. Regarding medium, the inhibitory mould agar (IMA), Sabouraud dextrose agar Emmons (SDAE), and malt-yeast agar (MYA) were tested and results showed that 55.6% of moulds were isolated using IMA, 18.5% using SDAE, and only 3.2% with MYA [ 50 ]. This study showed that SDAE, the often-used culture medium to isolate moulds, did not meet the expectations.…”
Section: Methods Used For Proven Diagnosismentioning
confidence: 99%
See 3 more Smart Citations